PEMIKIRAN ETIKA MURTADA MUTHAHHARI - Muammar A. Wahid; Hamzah Harun (Sulesana, 2025)
This study aims to analyze the thoughts of Murtada Muthahhari. Murtadha Muthahhari is a Muslim scholar, thinker, and intellectual from Iran who was very influential in the 20th century. Muthahhari is known as one of the important figures in the development of modern Islamic thought and the Islamic revolution in Iran. Murtadha Muthahhari's thoughts on the philosophy of justice are very profound and are one of his important contributions to the world of modern Islamic thought. For Muthahhari, justice is not just an abstract normative concept, but a fundamental value that is the core of social, political, and religious life. Muthahhari's thoughts on Islam and modernity emphasize that Islam is not a religion of the past that must be abandoned for the sake of progress, but a religion that contains principles that can guide humanity in answering modern problems.